Typological seismic fragility assessment of old railway stations by nonlinear time history analysis. Issue 12 (12th October 2021) - Rota, M.; Bracchi, S.; Iorio, D.; Penna, A.
Abstract: The homogeneity of standard Italian railway stations in terms of period of construction (second half of the 19th century), architectural and structural features, typical dimensions and morphology (mostly depending on expected number of passengers) allows the identification of building typologies, with an expected similar behaviour under seismic actions. Four typologies of standard railway stations were identified and, for each of them, variability in building geometry and material parameters was accounted for. Fragility curves were then derived by means of multi-stripe nonlinear dynamic analyses on equivalent-frame 3D macroelement models of the structures, for appropriately selected limit states. The results obtained can be very useful for assessing the seismic vulnerability of this kind of structures, whose seismic behaviour is of strategic importance, both for the potentially high number of victims and for the need of keeping railway lines operational in the aftermath of a seismic event. Also, the results presented in this study could be useful to set prioritization schemes of retrofitting interventions, starting from the identification of the stations most at risk, by combining fragility curves and seismic hazard information.